A Study on Channel Polling Mechanisms for the MAC Protocols in Wireless Sensor Networks. (15th December 2015) - Siddiqui, Shama; Ghani, Sayeed; Khan, Anwar Ahmed
Most research done on the channel polling mechanisms for WSN MAC protocols has focused on achieving efficiency in terms of optimizing either delay or energy performance. This study introduces the mechanism of altering the polling interval distribution for the MAC protocol, based on the application's optimization objective (delay or energy). Two options have been considered for both packet interarrival and polling interval distributions: deterministic and exponential, and their impact on performance analysis has been studied. The packet aggregation and block acknowledgements transmission schemes have also been incorporated in the performance analysis. Simulations for energy consumption and delay have been performed using MATLAB, for various combinations of interarrival and polling interval distributions. Results show that the energy consumption improves for the exponentially distributed polling intervals, while deterministic polling intervals provide better delay performance. Changing values of traffic load and packet aggregation demonstrate the trade-off between delay and energy consumption. The impact of aggregation on the error probability and subsequently on delay and energy has also been illustrated in simulations. Finally, optimal operating parameters have been studied in order to combine delay and energy consumption as optimization criteria.